(untitled) (LEARNing Landscapes, 2011)
The authors explore the assumption that intelligence is static through a case study of one student with special needs, demonstrating how a growth-oriented paradigm supports students. With a growth mindset, teachers can build the necessary confidence for students to risk learning through scaffolding the emotional, social, and cognitive components of learning.